2011
DOI: 10.1071/ch10459
|View full text |Cite
|
Sign up to set email alerts
|

A Series of 2D and 3D Novel Lanthanide Complexes Constructed from Squarate C4O42–: Syntheses, Structures, Magnetic Properties, and Near-infrared Emission Properties

Abstract: The solvothermal combination of trivalent lanthanide metal precursors with a squarate ligand (H2C4O4, 3,4-dihydroxy-3-cyclobutene-1,2-dione) has afforded the preparation of a family of eight new coordination polymers, [Ln2(C4O4)3(H2O)4] (Ln = La–Nd, Ho) (1–5), [Ln2(C4O4)3(H2O)8] (Ln = Er, Dy) (6, 7), and Tb2(C4O4)2(C2O4)(H2O)4 (8). Structural analysis reveals that the squarate ligand displays versatile coordination modes to generate novel 2D and 3D frameworks. Three new coordination modes, a bidentate/monodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Cyclic oxocarbon acids, such as squaric acid (H 2 C 4 O 4 , 3,4-dihydroxycyclobut-3-ene-1,2-dione), are of interest because of their cyclic structures, aromatic nature, wide-ranging chemical and physical properties leading to a variety of materials applications, , and varying coordination modes in coordination and structural studies. These varying coordination modes (variable denticities and bridging abilities) are attractive for the potential to produce novel extended networks. Squarate was chosen as a ligand of interest here because of its unique coordination modes and the fact that its aromatic/delocalized bonding makes the oxo donors of the ligand “softer” (under the Pearson definition) than would otherwise be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic oxocarbon acids, such as squaric acid (H 2 C 4 O 4 , 3,4-dihydroxycyclobut-3-ene-1,2-dione), are of interest because of their cyclic structures, aromatic nature, wide-ranging chemical and physical properties leading to a variety of materials applications, , and varying coordination modes in coordination and structural studies. These varying coordination modes (variable denticities and bridging abilities) are attractive for the potential to produce novel extended networks. Squarate was chosen as a ligand of interest here because of its unique coordination modes and the fact that its aromatic/delocalized bonding makes the oxo donors of the ligand “softer” (under the Pearson definition) than would otherwise be expected.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous work [11,12,27,28], several pseudo-polymorphs are separated depending on the bridging mode of sq and the number of solvent (water) molecules ligating to metal ions and incorporated as a guest: [{Ln2(sq)3(H2O)4}n], [{Ln2(sq)3(H2O)11}n] . (H2O)2, [Ln(Hsq)(sq)(H2O)6], [Ln(Hsq)(sq)(H2O)6] .…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the space groups reported were controversial; P21/c was chosen for Gd-sq [14] with one sq missing, presumably owing to disordered weak electron density. For Dy-and Er-sq [28], P21/c was assumed, but a severe overlap of the atomic coordinates remained. We encountered a similar centrosymmetry/non-centrosymmetry problem, and finally concluded that the most plausible space group is Pc based on the rational crystal structure (Figure 1b,c).…”
Section: Resultsmentioning
confidence: 99%
“…Compared 1 , 2 and the other Ho(III)-squarate polymeric framework, [Ho 2 (C 4 O 4 ) 3 (H 2 O) 4 ] n ( 3 ), synthesized under solvothermal condition reported in the previous literature [66]. The Ho(III) ions in 1 an 2 are both eight-coordinate, but, in 3 , is nine coordinate with a tricapped trigonal prismatic coordination environment.…”
Section: Resultsmentioning
confidence: 99%
“…The squarate, C 4 O 4 2− , has been widely used as a polyfunctional ligand, including (1) acts as a bridging ligand with various coordination modes (μ 2 to μ 6 bridges shown in Scheme 1) to build up many coordination polymers with novel extended networks, including 1D chain, 2D layer, 3D cube- and cage-like frameworks and so forth and (2) behaviors as hydrogen bond donor, acceptor or π−π constructor for the assembly of extended supramolecular architecture [30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. In the previous investigation, several 2D and 3D LnMOFs constructed via the bridges of lanthanide and squarate ligand with various coordination modes have been synthesized under hydrothermal or solvothermal conditions [64,65,66,67,68,69,70]. Their thermal behavior, magnetic property and photo-luminescence spectra of 2D and 3D LnMOFs have also been studied.…”
Section: Introductionmentioning
confidence: 99%